Kann das doch weg? Dealing with the German Modal Particle doch in Albanian Literary Texts’ Translation - Blertë İsmajli; Vjosa Hamiti (Studien zur Deutschen Sprache und Literatur)
In linguistics, the translatability of the German modal particles is considered a popular study object, particularly because of their rendering in “particle-poor” languages. Thus, the present study examines the translatability of the modal particle doch in Albanian literary texts. Compared to German language, Albanian does not have a group of modal particles and can, therefore, be classified as a “particle-poor” language. In general, (inter)subjective language elements in Albanian, such as modal particles in this case, come to a full meaning only in the context of use. Therefore, the translation must take the context into account. When translating from German to a particle-poor language, other means of expression, such as morphological, prosodic patterns, or a combination of these elements, available in the language are chosen to express the particular modal nuance. These expressions can also include contextual-pragmatic means and the use of extra-linguistic factors such as intonation, voice pitch, sentence accent, gestures, and facial expressions. This empirical corpus analysis is based on two novels: Franz Kafka’s “The Trial” (Der Prozess) and Hermann Hesse’s “Siddhartha - A Poem of India” (Siddhartha – eine indische Dichtung), and their two sets of translations into Albanian. Examining two translations of the same literary text allows for a better understanding of the lexical and syntactical means used in Albanian to render the modal particle doch. During the corpus analysis, the translation equivalents of doch in Albanian were extracted and classified into omission, transposition, paraphrasing, and word-for-word translations, based on the common translation-theoretical definitions.